The EU ETS and firm profits: An ex-post analysis for Swedish energy firms - Haisan Yu (Uppsala University, Department of Economics, 2011)
In January, 2005, the EU launched the first international emissions trading system (EU ETS), aimed at reducing carbon emissions in a cost-effective way by means of a market-based instrument. In this paper, we use the treatment/control, before/after design of the natural experiment approach to investigate the treatment effect of the EU ETS on the profitability of a sample of Swedish energy firms in 2005 and 2006. We also investigate whether under-cap and over-cap firms respond differently to the EU ETS. The estimation results in general suggest no significant impact in 2005 and a negative significant impact in 2006. The sub-sample analysis suggests that profitability of under-cap and over-cap firms were affected differently by the EU ETS in 2005, but not in 2006.
urn:nbn:se:uu:diva-144938
Keywords: D22; Q50; Q58; 330; EU ETS; difference-in-differences; fixed effect; Emissionshandel; EU-Umweltpolitik; Wirkungsanalyse; Rentabilität; Energiewirtschaft; Schweden